(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at investigating future anxiety and its relationship with the psychological stress on a sample of Tishreen University students. Furthermore, the study attempted to explore whether students differ according to their gender in the future anxiety and the psychological stress. The sample comprised of (188) students: (95 male and 93 female). In order to achieve the goals of this study the Inventory of University Students’ Anxiety Future was constructed. The final version of the scale consisted of (28) items. And the Inventory of University Students’ Sources of psychological stress was constructed, the final version of the scale consisted of (60) items. The results showed: there are correlation statistically significant between the future anxiety and the psychological stress. The results also indicated to significant differences (α≤ 0.05) between males and females means in the psychological stress, and its indicated to no differences between males and females in the future anxiety.